(untitled) (CIPEEX, 2025)
This article deals with Agrarian Law and Law applied to Agribusiness, exploring its concepts, classifications and legal implications. Initially, the concept of agribusiness or agribusiness is presented, defined as the agricultural relationship between law and agribusiness, which significantly demonstrates the importance of regulating land and its agricultural activity. It aims to present the correlation between land ownership and ownership, agrarian contracts and also the rights of rural workers. The methodology used was qualitative research into doctrines and participation in the VI National Congress of Agrarian Law. Among the results, it is highlighted that agribusiness is related to a group of economic activities associated with production, distribution and marketing. It is understood that agrarian law is connected to the legal regulation of land and its activity in the production of inputs, it does not only cover agriculture and livestock, but production and industry processes. It is concluded that agribusiness brings food security, where it is responsible for feeding many people around the world, supplying both the domestic and foreign markets. It is also worth highlighting that agribusiness is one of the country’s economic pillars, bringing local sustainability. The concept of Agribusiness or agribusiness was a term founded by jurist and economist Dr. Ray Goldberg who defined it as a term that refers to the set of economic attributions, which is a production chain in the agricultural sector, a very clear example is the production of inputs which takes place through a series of stages, including cultivation and harvesting, industrialization, distribution and commercialization. Law applied to agribusiness is a relatively new branch among the applied human sciences, requiring more dedication and academic encouragement.